Pengaruh Informasi Laporan Arus Kas dan Kepemilikan Institusional Terhadap Volume Perdagangan Saham Perusahaan Kategori Jakarta Islamic Index - Clarisa Nabila Putri; Destian Arshad Darulmalshah Tamara; Nur'aeni Nur'aeni (Journal of Applied Islamic Economics and Finance, 2022)
The research was to ascertain how cash flow statement information and institutional ownership affected the amount of stock trading. The method used is a quantitative research methods with descriptive and associative methodologies. The object of research in this study is the Jakarta Islamic Index with a period from 2016 to 2020. Purposive sampling was used to determine the sample data, and a total of 12 companies made up the sample. Secondary data from the annual financial reports of the companies obtained from each company's official website, the IDX, and the OJK were used in this study. Panel data regression analysis statistical using statistical data processing tools is the study model employed. The results of this research are the variables of cash flow, operating, investment, and financing cash flows, institutional ownership, have no simultaneous impact on stocks trading volume. However, only institutional ownership partially has no effect on stocks trading volume.